The Correlation between Medical Personnel’s Attitude and Pap Smear Examination Practice at Islamic Sultan Agung Hospital Semarang - Zulaikhah, Siti Thomas; Surani, Endang; Anggorowati, Eka Norma (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Introduction: Cervical cancer is still ranked in the first place of those diseases most commonly developing in Indonesian women. It is predicted that 41 new cases occur every day, and around 20 people every day pass away of it. Cervical cancer keeps increasing because the coverage of screening through pap smear examination is low. Objective: This research aims at discovering the correlation between medical personnel’s attitude and practice of pap smear examination at Rumah Sakit Islam Sultan Agung (RISA) Semarang. Methods: The study is observational research using cross sectional design with a sample of 38 medical personnel taken randomly from 273 personnel as its population in RISA Semarang. The data are taken using questionnaire and interview with respondents, and the obtained data are analyzed using univariate and bivariate tests, using chi-square test, at a significance level < 0.05. Result: the percentage of medical personnel having regular pap smear practice is higher in medical personnel with good attitude (66.7%) compared to those with poor attitude (17.6%). The data analysis using Chi Square statistic test indicates a significant difference, p = 0.003.Conclusion: the results of this reseach show that pap smear is more commonly done by those medical personnel with good attitude than those with poor attitude